Evaluation of teaching methodologies in pharmacology for undergraduates: a cross-sectional analysis in a medical college of South India - Ghazala, Zainab; Kalshetty, Prakash; Vardhamane, Shrenik (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Pharmacology is an important part of medical education. A competent doctor should be able to prescribe rational treatment to the patients to minimise the adverse effects and contribute to the improvement of overall healthcare system. There is a dire need to reform the undergraduate pharmacology curriculum to match up to the rapidly evolving medical field. Feedback system is one of the most successful instruments in improving any system. We have undertaken a similar feedback system to study the advantages and disadvantages of various study methods for teaching theory and practical exercises to the medical undergraduates. Methods: This is a cross sectional questionnaire based study conducted in the department of pharmacology. Students of MBBS 2nd year were enrolled into the study. The purpose of the study was explained to them and clarifications were made if any. The questionnaire included questions on various aspects of teaching methodology and graded by students on internationally accepted ‘Likert’ scale. Results: In our study students favoured teaching by blackboard method (96%) and many preferred a combination of blackboard and power point presentation. Discussing on issues of clinical significance of the topic was favoured by 96% of the students and 67% students responded that stressing on the facts concerned with Post graduate entrance exams is more important. Sixty nine percent and 85% students preferred short essays and MCQs respectively as method of evaluation and 68% of them favoured evaluation by both the methods. Regarding pharmacology practical exercises most of the students preferred clinical problems, dosage calculation, ADR reporting and other problem based learning techniques. Studying pharmacology as an integrated subject with other clinical subjects was preferred by 68% of the students. Conclusions: It is well known that students learn better when they are involved actively in learning process than when they are passive recipients. In our study we realised that undergraduate pharmacology teaching pattern should be modified mostly towards pharmacotherapeutics and clinical pharmacology.